Technology-centred learning processes as digital artistic development: On the reciprocal effects of conceptual models, metaphors and presets. Issue 2 (1st December 2021) - Neuhausen, Timo; Wernicke, Carsten; Ahlers, Michael
This case study looks at a self-directed learning process of a professional classical-trained musician adopting a previously unknown digital-material musical device. In order to achieve the desired artistic result, the musician has to modify his music-related action in favour of the device's calls for action, which are shown to him by a preset session. For this purpose, a specific interface relation must be established in the connection between the user and the device. The case study is contrasted with data from its framing research project. Findings include aspects as affirmation or degrees of unfamiliarity and their respective impacts on the subject's action repertoires. A model of learning in the context of digital media or interfaces is introduced and discussed. It offers a specific potential for identifying particularities of how meaning and functionality of digital-material musical devices are embedded into everyday artistic contexts.